2019
DOI: 10.1097/gox.0000000000002082
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Postoperative Narcotic Use in Prepectoral Versus Dual-plane Breast Reconstruction Following Mastectomy

Abstract: Background:The majority of postmastectomy breast reconstruction performed in the United States is device-based. Typically, a tissue expander or implant is placed in the dual-plane (ie, subpectoral). Prepectoral breast reconstruction with acellular dermal matrices following mastectomy is a relatively new technique that has favorable outcomes with minimal complications and satisfactory aesthetic results. Few studies have compared opioid use between the 2 approaches. This study compares duration of postoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…Yet, previous studies have indicated that the incidence of pain after cancer surgery is significantly higher when breast reconstruction is performed, especially following the SP approach, with 49% of patients experiencing upper body acute and chronic pain syndrome [ 23 , 24 ]. Plachinski et al [ 21 ] found similar results, with no significant difference in pain scores between the two cohorts and that the evaluation of pain should be more inclusive of other intrinsic criteria such as chronic pain, comorbidities, age, and BMI, in opposition to most of the previous studies [ 15 , 25 , 26 ]. Lee et al [ 20 ] observed a significant difference in favor of the PP group when pain was assessed during shoulder motion two weeks postoperatively, and, interestingly, the scores of shoulder disability were significantly higher in the SP group.…”
Section: Discussionmentioning
confidence: 85%
“…Yet, previous studies have indicated that the incidence of pain after cancer surgery is significantly higher when breast reconstruction is performed, especially following the SP approach, with 49% of patients experiencing upper body acute and chronic pain syndrome [ 23 , 24 ]. Plachinski et al [ 21 ] found similar results, with no significant difference in pain scores between the two cohorts and that the evaluation of pain should be more inclusive of other intrinsic criteria such as chronic pain, comorbidities, age, and BMI, in opposition to most of the previous studies [ 15 , 25 , 26 ]. Lee et al [ 20 ] observed a significant difference in favor of the PP group when pain was assessed during shoulder motion two weeks postoperatively, and, interestingly, the scores of shoulder disability were significantly higher in the SP group.…”
Section: Discussionmentioning
confidence: 85%
“…Overall, it was found that patients undergoing prepectoral reconstruction used opioids of 33% fewer days than those who underwent dual-plane reconstruction, suggesting that this surgical approach may be associated with reduced chronic postoperative pain. However, this study was limited by the lack of data on nonopioid medication consumed by patients [25]. In another study of 2207 women undergoing breast reconstruction, patients with deep inferior epigastric perforator (DIEP) flaps or superficial inferior epigastric (SIEA) perforator flaps had less pain 1 week postoperatively compared to tissue expanders/implant reconstruction on the McGill Pain Questionnaire-Sensory scale (p \ 0.01, p = 0.02).…”
Section: Surgical Factorsmentioning
confidence: 99%
“…While other studies have shown reductions in postoperative opioid use in patients receiving prepectoral TEs, 23 to the best of our knowledge, this is the largest study to demonstrate a decrease in acute, inpatient opioid use following immediate prepectoral tissue expander placement. Prepectoral patients required on average 22 OME less than their subpectoral counterparts—the equivalent of nearly 15 mg of oral oxycodone.…”
Section: Discussionmentioning
confidence: 66%